2017
DOI: 10.1111/ejh.12980
|View full text |Cite
|
Sign up to set email alerts
|

Increasing incidence of primary central nervous system lymphoma but no improvement in survival in Sweden 2000‐2013

Abstract: Objectives: This study aims to characterize the epidemiology of immunocompetent Primary central nervous system lymphoma (PCNSL) diagnosed 2000-2013 in Sweden.Methods: Cases were identified in the population-based Swedish Lymphoma Register.Incidence per 100 000 person-years and 95% confidence intervals (CI) were calculated, and PCNSL-specific survival was estimated using relative survival. Tests for temporal trends were performed using Poisson regression. Population incidence of all brain tumors was retrieved f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 26 publications
0
39
0
2
Order By: Relevance
“…Therefore, this may offer a plausible explanation for why new treatments have not translated into a survival benefit in the group of PCNSL (27). Furthermore, it is likely that the different types of treatment approaches and also the presence of immunocompromised patients played a role as confounding factors in our analysis.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore, this may offer a plausible explanation for why new treatments have not translated into a survival benefit in the group of PCNSL (27). Furthermore, it is likely that the different types of treatment approaches and also the presence of immunocompromised patients played a role as confounding factors in our analysis.…”
Section: Discussionmentioning
confidence: 98%
“…Despite improvements in chemotherapy protocols, patients with primary CNS lymphomas (PCNSL) still have a dismal prognosis (1,2). Standard chemotherapy protocols which are effective for systemic non-Hodgkin lymphomas, such as CHOP or CHOD have inferior effect in PCNSL, presumably reflecting the difficulty of penetration of the blood-brain barrier (BBB) by most chemotherapeutic agents (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…The authors showed the increasing PCNSL incidence rate and the possible correlation of this increase with the increasing number of immunosuppressed patients. This appealing issue was confirmed in a recently published paper that reported a current Swedish scenario in which the increasing trend was mostly observed among elderly individuals [ 2 ].…”
mentioning
confidence: 63%
“…онкологии, лучевой диагностики и терапии и радиационной медицины, ГВУЗ «Тернопольский государственный медицинский университет имени И. Я. Горбачевского МЗ Украины». Список літератури [1]…”
Section: сведения об авторахunclassified
“…У другому десятилітті XXI ст. відзначають світову тенденцію до стрімкого підвищення рівня лімфопроліферативних захворювань, серед них усе більшої питомої ваги набувають негоджкінські лімфоми, що перебігають з екстранодальними ураженнями [1,2].…”
unclassified